2013
DOI: 10.1021/ja4057807
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging Agents for Alzheimer’s Disease: Copper Radiopharmaceuticals that Target Aβ Plaques

Abstract: One of the pathological hallmarks of Alzheimer's disease is the presence of amyloid-β plaques in the brain and the major constituent of these plaques is aggregated amyloid-β peptide. New thiosemicarbazone-pyridylhydrazine based ligands that incorporate functional groups designed to bind amyloid-β plaques have been synthesized. The new ligands form stable four coordinate complexes with a positron-emitting radioactive isotope of copper, (64)Cu. Two of the new Cu(II) complexes include a functionalized styrylpyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 77 publications
(156 reference statements)
3
117
1
Order By: Relevance
“…[24] It is noteworthy that exploration of the “metal hypothesis of AD” with PET is actively pursued by several laboratories, with recent accounts of carbon-11 and fluorine-18 labeled analogs of L2-b ( N 1 , N 1 -dimethyl- N 4 -(pyridin-2-ylmethyl)benzene-1,4-diamine)s[25] and copper-64-labeled bis(thiosemicarbazonato)Cu II complexes. [26,27]…”
Section: Introductionmentioning
confidence: 99%
“…[24] It is noteworthy that exploration of the “metal hypothesis of AD” with PET is actively pursued by several laboratories, with recent accounts of carbon-11 and fluorine-18 labeled analogs of L2-b ( N 1 , N 1 -dimethyl- N 4 -(pyridin-2-ylmethyl)benzene-1,4-diamine)s[25] and copper-64-labeled bis(thiosemicarbazonato)Cu II complexes. [26,27]…”
Section: Introductionmentioning
confidence: 99%
“…218 It is widely accepted that amyloid peptides are formed by the cleavage of amyloid precursor protein (APP) by various secretase enzymes. 252 It was also found that these processes can be suppressed by the wellknown copper chelator D-penicillamine.…”
Section: Thermodynamic Kinetic and Structural Studies On The Metal Cmentioning
confidence: 99%
“…More recently a novel metal imaging PET approach has been developed, using radioactive coordination bis(thiosemicarbazonato)copper complex of 64 Cu. This targets copper homeostasis and has been designed to bind selectively to amyloid plaques (Hickey et al, 2013). Copper radiolabels are essential for increasing our understanding on of the mechanisms of copper dyshomeostasis in AD.…”
Section: General Overview Of Elemental Imaging Techniques For Biologimentioning
confidence: 99%